The Limits To Estoppel: Flexibility And Unconscionability - Hopkins, Nicholas (Journal of Malaysian and Comparative Law, 1999)
This paper advises caution in giving the doctrine of estoppel too broad a scope. The flexibility and wide utility of estoppel, referred to by the Federal Court in Boustead Trading (1985) Sdn Bhd v Arab-Malaysian Merchant Bank Bhd, make it essential to define the limitations to the doctrine. This need for caution will be highlighted by considering the role of unconscionability in estoppel claims and by defining the circumstances in which estoppel is the appropriate response to unconscionable conduct. As a preliminary point, it should be noted that unconscionability is being discussed here in connection with the creation of rights. This is conceptually different to the other use of unconscionability as a factor vitiating an existing contractual agreement.